Computational design of newly engineered DARPins as HER2 receptor inhibitors for breast cancer treatment - Maryam Beheshti Isfahani; Karim Mahnam; Hooria Seyedhosseini-Ghaheh; Hamid Mir Mohammad Sadeghi; Hossein Khanahmad; Vajihe Akbari; Jaleh Varshosaz (Research in Pharmaceutical Sciences, 2023)
Background and purpose: Human epidermal growth factor receptor 2 (HER2) is overexpressed in approximately 25% of breast cancer patients; therefore, its inhibition is a therapeutic target in cancer treatment. Experimental approach: In this study, two new variants of designed ankyrin repeat proteins (DARPins), designated EG3-1 and EG3-2, were designed to increase their affinity for HER2 receptors. To this end, DARPin G3 was selected as a template, and six-point mutations comprising Q26E, I32V, T49A, L53H, K101R, and G124V were created on its structure. Furthermore, the 3D structures were formed through homology modeling and evaluated using molecular dynamic simulation. Then, both structures were docked to the HER2 receptor using the HADDOCK web tool, followed by 100 ns of molecular dynamics simulation for both DARPins / HER2 complexes. Findings/Results: The theoretical result confirmed both structures' stability. Molecular dynamics simulations reveal that the applied mutations on DARPin EG3-2 significantly improve the receptor binding affinity of DARPin. Conclusion and implications: The computationally engineered DARPin EG3-2 in this study could provide a hit compound for the design of promising anticancer agents targeting HER2 receptors.